Porphyrinoid functionalized carbon nanomaterials for cancer therapies - Monteiro, Ana Rita Rodrigues Vilares Cabral (2023)
The quest for more effective cancer therapies is an ongoing and pressing challenge, as cancer remains one of the leading causes of mortality worldwide. This thesis explores the anticancer potential of new systems comprising carbon nanomaterials (as graphene oxide, GO, and graphene quantum dots, GQDs) and porphyrinoids (as porphyrins or phthalocyanines, Pcs). The new hybrid materials were characterized and tested in photodynamic therapy (PDT) or in deoxyribonucleic acid (DNA) G-quadruplex (G4) sensing and stabilization. Therefore, a comprehensive review of the state of the art was carried out initially, to understand the synthetic routes used to functionalize GO/GQDs with organic molecules (namely porphyrins and Pcs) through covalent and non-covalent bonds. The application of these systems in different cancer therapies was also summarized. The reported potential alongside with the detected gap in the knowledge allowed to define and justify the objectives of this thesis. Several porphyrins were synthesized, bearing structural features considered to be adequate to functionalize carbon nanomaterials. On a first approach, symmetric tetracationic porphyrins, such as 5,10,15,20-tetrakis(1-methyl-pyridinium-4-yl)porphyrin (TMPyP), its Zn(II) complex (Zn-TMPyP) and a dibenzoporphyrin (P1-C5), were successfully obtained through conventional synthetic pathways involving, for example, Rothemund and Heck reactions and cationization through N-alkylation. On a second approach, several attempts were explored to functionalize the meso position of porphyrins’ macrocycle with terpyridine (tpy) units through Vilsmeier-Haack formylation, Suzuki-Miyaura coupling and Kröhnke-type reactions, among others. The synthesized tetracationic porphyrins (TMPyP, Zn-TMPyP and P1-C₅) were loaded onto GO/GQDs and the resulting hybrids were characterized by several spectroscopic techniques and electron microscopy. The new systems showed photo-antiproliferative activity in T24 human bladder cancer cells. Within this research context, Zn-TMPyP@GQDs were found to be the most promising hybrid nanomaterials. In a different application, four Zn(II) complexes of cationic Pcs (ZnPcs) were assembled on GO to develop multifunctional G4 optical sensors, based on a “turn-off-on” effect of their fluorescence properties. When compared with non-immobilized ZnPcs, ZnPcs@GO allowed to detect and stabilize G4s for longer periods, through a progressive release of ZnPcs from GO platforms and concomitant fluorescence recovery. A novel approach was developed to synthesize functional hybrid nanomaterials, in which blue- or aqua green-emitting GQDs (GQDs-B/AG) were covalently attached to DNA sequences with the potential to fold as G4s. GQDs induced the luminescence and shaped the folding properties of the new arrays. The GQDs-DNA bioconjugates showed a higher potential to carry the porphyrin TMPyP, in comparison to the affinity between non-immobilized DNA sequences and TMPyP. Lastly, this thesis describes frontier research about more complex hybrid nanomaterials, comprising GO sheets functionalized with 5,10,15,20-tetra(pyridin-4-yl)porphyrin (TPyP) and gold nanoparticles (AuNPs). Despite its exploratory character, the presented research suggests that the porphyrin TPyP allows a higher organization of AuNPs over the GO sheets. Overall, the results obtained and discussed throughout this thesis highlight the potential of carbon nanomaterials to stabilize different types of porphyrinoids and boost their action in cancer therapies related to PDT or G4s. The as-found synergies show that this type of hybrid materials deserves further exploration towards future biomedical applications.